Multiply the polynominal expression (x + 2)(x - 4)

1 answer

To multiply the polynomial expressions \((x + 2)(x - 4)\), you can use the distributive property (also known as the FOIL method for binomials). Here’s how it works step-by-step:

  1. Multiply the first terms:
    \(x \cdot x = x^2\)

  2. Multiply the outer terms:
    \(x \cdot (-4) = -4x\)

  3. Multiply the inner terms:
    \(2 \cdot x = 2x\)

  4. Multiply the last terms:
    \(2 \cdot (-4) = -8\)

Now, combine all these results together:

\[ x^2 - 4x + 2x - 8 \]

Next, combine like terms:

\[ x^2 + (-4x + 2x) - 8 = x^2 - 2x - 8 \]

So, the product of the polynomial expression \((x + 2)(x - 4)\) is:

\[ \boxed{x^2 - 2x - 8} \]